Perancangan Website Pencatatan Kehadiran Bertugas Anggota Putra Altar Santo Tarsisius Gereja Santa Maria Imakulata - Amadeus Stevan Beale; Wasino (Jurnal Ilmu Komputer dan Sistem Informasi, 2025)
Misdinar at Santa Maria Imakulata Church, called the Altar Boy of Saint Tarsisius, is a group in charge of assisting the Priest at the Church Altar during a Eucharistic celebration. At this time, Putra Altar Santo Tarsisius still records attendance on duty manually using Google Forms so that it is considered less efficient in recording the attendance of members on duty. So in this study, a website design was carried out to record the attendance of members on duty with the aim of assisting in recording the attendance of members after each duty. The scrum method is used in designing this website and using the Laravel framework and MySQL database.